The shortest time to reach maximal oxygen uptake without prior warm up in professional soccer players - Gatterer, H.; Faulhaber, M.; Klausner, F.; Burtscher, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In very heavy exercise, preceded by adequate warm-up, VO2max and HRmax can be attained within one minute (Astrand et al., 2003). However, with a restricted warm up, VO2 during short exhaustive treadmill runs of ~2min duration (i.e. 800 m run) was shown to plateau at different levels below VO2max depending on pacing strategies (Sandals et al., 2006). The question arises about the shortest time to achieve VO2max with optimal pacing and without a preceding warm up. Methods: Eight professional male soccer players, accustomed to sprint training, performed a progressive paced field test to exhaustion consisting of two laps on a track (first lap 50%, half lap 70% of the self estimated maximal performance capacity followed by an all-out sprint to the finish line) and an incremental treadmill test (work increments of 1 km/h per minute). Oxygen uptake, minute ventilation and heart rate were measured with a portable spirometric-telemetric device (Oxycon mobile, Jäger, Germany). In the 3rd minute after cessation of work, blood lactate concentrations were determined. Results: The highest VO2 values in the field test were achieved after 230±17s. When using 30 s averages of data collection VO2max values differed significantly between the field and the lab test, however no differences were found for the 15 s averages (r=0.824 (p<0.05)). The total errors of estimation for the field test were 2.6 and 1.8 ml/min/kg for the 30 and 15 s averages, respectively. Lactat concentrations in the lab test were significantly lower than in the field test. Discussion: These results demonstrate that a test duration of approximately 230s without warm up is sufficient for eliciting VO2max in professional soccer players, provided a progressive pacing strategy is applied. An explanation for the rapid attainment of VO2max may be that the relative intensive "warm up" run (first 1.5 laps) speeds up (Gerbino et al., 1996) or increases the primary VO2 response amplitude (Burnley et al., 2001) of the 200 m run to exhaustion. Furthermore the progressively increasing speed in contrast to other pacing strategies lengthens running time so that the slow component of the VO2 increase can occur and possible O2 delivery limitation due to reduced muscular temperature or pH changes is avoided (Burnley et al., 2001).